Online-based English Reading Learning Model in the New Normal Era (Post-Pandemic Covid-19) - Atmowardoyo, Haryanto; Sakkir, Geminastiti (Celebes Journal of Language Studies, 2023)
This article is part of research entitled "Online-based Student English Learning Models in Facing Curriculum Changes in the New Normal Era." This research was conducted to see and identify online-based reading learning models for students. The research method is a descriptive qualitative method using a questionnaire and the final assignment of the Project course (Lesson Plan and Instruction). The number of samples used was 52 students who took the Project course (Lesson Plan and Instruction). Of the 52 students, 7 students chose to teach the reading skill. Data analysis includes observation, open coding, and axial coding. The results reveal that the media used by students in learning reading skills is divided into online media 57.14% (4 students) and 42.85% offline (3 students) in learning reading skills. Applications used by students in learning reading are divided into Zoom, face-to-face/ offline, Quizzes, PPT, and YouTube. The learning methods that students apply in learning reading are Communicative Language Teaching (14.28%), Guided Discovery Learning (14.28%), Audio Lingual Method (14.28%), Suggestopedia (14.28%), Discovery Learning (14.28%), Total Physical Response (14.28%) and Community Language Learning (14.28%). The topics presented included: Comparison; Narrative text; Personal Letters; Description, and Notice.